Beautiful Justice: The Role of Aesthetic Beauty in Restoring Transcendent Connection - Vasintha Pather (South African Journal of Arts Therapies)
This article seeks to illuminate how colonial and apartheid systems dispossessed people of colour in South Africa of the natural and cultural beauty inherent in their ancestral, socio-cultural and/or lived environments. It underscores how these systems forced people into survival conditions that hindered their capacity to cultivate beauty in their surroundings, cultural practices, and inner lives. Beauty, which often plays a central role in fostering psycho-spiritual development and connection, was systematically disrupted, distorted, and undermined. Within the arts therapies, there lies a unique potential to address these intergenerational disruptions by facilitating experiences of beauty as a pathway to restorative healing and justice.